Expedient in situ test techniques for predictive maintenance of rendered façades - Inês Flores-Colen (2006)
The practice of predictive maintenance (through periodic inspections) depends on the efficiency of in situ evaluations of the in-service performance of the constructive solutions, which in turn depends on a set of logical procedures inherent to a performance based methodology and a correct diagnosis. In situ tests are a precious auxiliary tool for visual inspections, since they allow the detection of gross diagnosis mistakes, reduce the subjectivity of visual inspections and enable a more accurate assessment of the real maintenance needs. These tests have limitations, however, and depend on the technique used (often the limited precision of a technique only allows a qualitative analysis) and the experience of the practitioners. In situ tests for rendered facžades include a variety of tests and techniques, most of them not standardised, and therefore a coherent and global classification is sometimes difficult to establish. In this paper a methodology for choosing the most adequate in situ techniques to diagnose in-service performance of rendered facžades is proposed. The subjects of this analysis were current and expedient techniques, used in several inspections performed in different renders, within the PhD research work of the first author. These techniques are classified and also characterised in terms of the data collected (parameters measured), their contribution to understanding in-service performance (analysis of relevant properties), the degradation state (anomalies and their causes) and their relation to maintenance needs. Finally, they are compared and rated using various criteria and evaluated in terms of their adequacy for in situ assessment.